Avaliação da expressão gênica de bombas de efluxo em Mycobacterium tuberculosis após exposição à rifampicina e verapamil em ambiente intramacrofágico - Canezin, Pedro Henrique (2017)
Tuberculosis (TB) is an infectious disease caused by the bacillus Mycobacterium tuberculosis (Mtb). Multidrug-resistant TB (MDR) is caused by rifampicin and isoniazid resistant Mycobacterium tuberculosis, while in the extensively resistant TB (XDR), the bacillus presents additional resistance to any fluoroquinolone and to at least one of the three second-line injectables (amikacin , Kanamycin or capreomycin). The growing recognition of MDR / XDR-TB has led to the development of new therapeutic strategies using new and old tuberculostatic drugs. In cases of MDR-TB, as well as for XDR-TB, specialized and individualized treatment is advocated. Mtb presents intrinsically resistance to some drugs by the constitution of membrane rich in fatty acids. Thus, the main mechanism of resistance involves mutations in genes involved in the metabolism of anti-TB drugs. Recently, the sequencing of the Mtb genome showed that the bacillus constitutively presents several efflux pumps (EPs) responsible for pumping ions, molecules and drugs out of the bacillary environment. There are substances capable of inhibiting this efflux system, causing the drug to remain within the bacillus and its death, such as Verapamil (VP). Some authors have reported a relationship between EPs and the ability of Mtb to overcome oxidative stress within macrophages. Therefore, the model of infection of THP-1 cells by Mtb has been used to evaluate the bacillary resistance after its exposure to the macrophagic environment. Thus, this study aimed to evaluate the gene expression of EPs in macrophagic environment at exposure to RIF, VP and RIF+VP in 24 h and 72 h. THP-1 cells were infected with Mtb H37Rv and exposed to RIF, VP and RIF+VP in 24 h and 72 h. The qPCR was performed using the master SYBR green PCR mix in the StepOne Real Time PCR System. At 24 h of drug exposure, an overexpression of the majority of BEs was observed in exposure to RIF, VP and RIF+VP. However, at 72 h there was an absence of expression of most BEs, including the RIF+VP combination. In this sense, additional in vivo studies could bring new information about the action of RIF+VP in the bacillus. Therefore, this combination could undoubtedly aid mtb-MDR therapy.